1996
DOI: 10.1084/jem.184.2.465
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells pulsed with RNA are potent antigen-presenting cells in vitro and in vivo.

Abstract: SulTlnlaryImmunization with defined tumor antigens is currently limited to a small number of cancers where candidates for tumor rejection antigens have been identified. In this study we investigated whether pulsing dendritic cells (DC) with tumor-derived P,.NA is an effective way to induce CTL and tumor immunity. DC pulsed with in vitro synthesized chicken ovalbumin (OVA) P, NA were more effective than OVA peptide-pulsed DC in stimulating primary, OVA-specific CTL responses in vitro. DC pulsed with unfractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
508
2
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 832 publications
(519 citation statements)
references
References 32 publications
3
508
2
6
Order By: Relevance
“…Although it is known for more than one decade that antigenencoding RNA co-incubated with APCs, is internalized and translated, 21 surprisingly few data are published on the underlying mechanisms in vitro and in vivo. The only study that investigated the uptake of RNA in vivo proposed a saturable Ca +2 ion-dependent process without defining the exact mechanism and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known for more than one decade that antigenencoding RNA co-incubated with APCs, is internalized and translated, 21 surprisingly few data are published on the underlying mechanisms in vitro and in vivo. The only study that investigated the uptake of RNA in vivo proposed a saturable Ca +2 ion-dependent process without defining the exact mechanism and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that DC pulsed with peptide of tumorassociated antigens, whole cell lysates, or RNA can trigger tumor-specific responses. [30][31][32] These approaches are currently limited in prostate cancer due to the lack of defined tumor antigens; the technical difficulties in obtaining sufficient amounts of mRNA; and limitations The T-cell stimulatory capacity of DC correlates with increased surface expression of MHC II and costimulatory molecules. 33 The upregulation of costimulatory molecules and MHC I/II of DC could enhance the immunogenicity of tumor antigens in poorly immunogenic cancers such as prostate cancer that are otherwise not recognized by immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the context of immunostimulation by CpG motifs, the persistence leads to overstimulation and toxicity [5,6]. Taking all these drawbacks into account, our group as well as others developed genetic vaccines using messenger RNA (mRNA) instead of plasmid DNA [7][8][9][10][11] (for a review on mRNA vaccines, see Pascolo [12]). mRNA are easy to manufacture in high amounts, to purify to homogeneity and to characterize.…”
Section: Introductionmentioning
confidence: 99%